Acuraria da ultrassonografia e eletroneuromiografia no diagnóstico da síndrome do tunel do carpo - Pimentel, Benedito Felipe Rabay [UNIFESP] (2016)
Introduction: The carpal tunnel syndrome, characterized by the compression of the median nerve at the wrist, is the most common compressive neuropathy of the upper limb. Although, it presents an inconsistent and controversial diagnosis and there is not an accepted standard reference (gold standard) in the literature. Objective: To evaluate the accuracy of ultrasonography and electromyography in the diagnosis of the carpal tunnel syndrome. Methods: It was included a total of 115 patients with high probability of clinical diagnosis for the carpal tunnel syndrome. All the patients underwent the ultrasonography and the electromyography, and, subsequently, underwent the surgical treatment. In order to define truly carpal tunnel syndrome patients, the remission of paresthesia after the surgery was considered as the reference standard (gold standard). The accuracy of the ultrasonography and the electromyography was measured by the evaluation of the results of these tests (positive or negative) according to the results of the surgery (remission or no paresthesia). Results: The accuracy of the ultrasonography and the electromyography in relation to the reference standard (gold standard) was, respectively, for sensitivity 84.6% and 92.3%, for specificity 81.8% and 90.9%, for positive predictive value 97.8% and 99.0%, for negative predictive value 36.0% and 55.6%, for positive probability ratio 4.7 and 10.2 and negative probability ratio 0.2 and 0.1. Conclusions: Ultrasonography and electromyography were effective to detect patients suffering from the carpal tunnel syndrome, but these tests were not effective to discard the suspicion of carpal tunnel syndrome.